Development of a Registered Nurse Competency Framework, Labour Room, Buddhachinaraj Phitsanulok Hospital - Dusitkul , Yaowarat; Chitpakdee, Bunpitcha; Akkadechanunt, Thitinut (Nursing Journal CMU, 2020)
The competency of registered nurses is important for human resource management and service quality development for pregnant women and fetuses to have a safe deliveries. The purpose of this development study was to develop a competency framework for registered nurses in labour room of Buddhachinaraj Phitsanulok Hospital by applying the stategies for developing competency framework of Marrelli, Tondora, & Hoge (2005). The population consisted of six nurses who are working in the labour room at Buddhachinaraj Phitsanulok hospital, and samples consisted of five experts. The instrument used for this study was an interview guideline validated by a panel of 3 experts. The data collection process included reviewing the literature, and interviewing nurses. Content analysis and item content validity index calculation of competencies were used for data analysis. The results of this study revealed that a competency framework for registered nurses in the labour room at Buddhachinaraj Phitsanulok hospital consisted of eight categories and 67 behavioral indicators which were 1) assessing health status of the pregnancy and fetus consisted of eight behavioral indicators, 2) nursing care for pregnant with complication consisting of five behavioral indicators, 3) promoting the progress of labour consisted of seven behavioral indicators, 4) nursing care for parturient consisted of seventeen behavioral indicators, 5) competency of conducting delivery consisted of nine behavioral indicators, 6) nursing care for neonatal consisted of fourteen behavioral indicators, 7) promoting breastfeeding consisted of three behavioral indicators and 8) caring for safety and risk management consisted of four behavioral indicators. Nurse administrators can apply this competency framework to create a performance evaluation criteria and to develop competency of registered nurses in the labour room at Buddhachinaraj Phitsanulok Hospital.